Coronavirus in the era of digital connectivity: Opportunities and challenges - (:unkn) unknown (WILEY, 2022)
In this article, we examine the opportunities and challenges digital connectedness creates in the fight against epidemics, in particular the coronavirus (COVID-19). We deduce that digital connectedness of individuals and organizations eased sharing of information on the causes and measures aimed at controlling and avoid the rapid spread of the epidemic in developing economies of Africa. We conclude that digital connectedness enabled African countries to access

share and implement globally suggested mechanisms aimed at controlling the spread of the COVID-19 epidemic. Future, studies should examine how African economies use digital connectedness to increase individual and organizational participation in curbing epidemics and also boost health management.
Keywords: AFRICAN-SWINE-FEVER